Market potential for sago starch and its derivatives in the Philippines - Fedillaga, Albert Joseph A.; Acuña, Thaddeus R.; Ramoneda, Brenda M.; Concepcion, Sylvia B.; Laorden, Nikko L. (2016)
In this chapter, we assess the market potential of sago and its derivative products in the Philippines by analyzing demand and import data of the current products that serve the needs of sago flour, starch, and its derivatives. We show that given the present market players in Southeast Asia, the best market potential of Philippine sago can be realized in the production of high-value starch derivatives such as lactic acid. Sago plantations can be developed for starch production, but the starch must be converted into high-value products in order to compensate for the costs of developing the plantation.
Keywords: Sago industry